Measuring the solubility product constant of paramagnetic cations using time-domain nuclear magnetic resonance relaxometry - Cobra, Paulo Falco; Gomes, Bruna Ferreira; Nascimento Mitre, Cirlei Igreja; Barbosa, Lucio Leone; Marconcini, Lucineia Vizzotto [UNESP]; Colnago, Luiz Alberto (Elsevier B.V., 2015)
The use of time-domain NMR relaxometry is already well established for determining the concentration of paramagnetic cations. Paramagnetic cations have unpaired electrons, and in aqueous solutions, they interact with hydrogen nuclei, changing the relaxation time of the solvent. Thus, a linear relationship can be established between the nuclear spin-lattice relaxation time, T-1, or the spin-spin relaxation time, T-2, and the concentration of paramagnetic ions in solution. Previous studies have shown the efficacy of using T-1 and T-2 for easily determining the titration equivalence point. Currently, the most practical method for determining T-2 is the Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence. Thus, in this paper, we used the T-2 relaxation time to determine the concentration of paramagnetic ions in solution. We used T-2 relaxometry as a simple and useful method for measuring the hydroxide solubility products (K-sp) of Fe(OH)(3), Cu(OH)(2) and Mn(OH)(2) aqueous solutions as functions of pH. To our knowledge, this is the first use of T-2 relaxometry to measure K-sp. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Time-domain nuclear magnetic resonance relaxometry; Paramagnetic cations; Titration; Solubility product